2018
DOI: 10.3390/min8110480
|View full text |Cite
|
Sign up to set email alerts
|

Controls on Barite Crystal Morphology during Abiotic Precipitation

Abstract: Barite (BaSO4) is a stable and widely distributed mineral in Earth’s crust. As such, barite has the potential to preserve specific geochemical and morphological characteristics representative of conditions at the time of its formation, which could be useful for interpretations of Earth’s ancient rocks and paleoenvironments. In this study, we used variations in saturation index, solution temperature, solution chemistry, presence of organics, and Mg2+ and Ca2+ ions to investigate variations in barite crystal mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
(122 reference statements)
1
14
0
Order By: Relevance
“…The texture and chemistry of this organic matter‐rich, texturally distinctive nano‐porous pyrite is consistent with an origin through sulfidization of biofilms as early as during stromatolite growth (c.f., Baumgartner, Van Kranendonk, et al, 2020; Baumgartner et al, 2019), as is supported by the presence of entombed, autochthonous organic matter strands and filaments that closely resemble variably degraded and remineralized EPS (compare the organic matter that is encrusted by barite micro‐spherulites in Figure 3f with organic matter strands in Baumgartner et al[2019, their Figure 4]). Hence, while all the physical and chemical factors that can control barite morphology are still not entirely understood (c.f., Widanagamage et al, 2018), our data suggest that intimately associated organics have been important factors for micro‐spherulite formation. These organics were likely derived from (decaying) ancient microbial mats that flourished in a hydrothermally influenced, low‐temperature, shallow water depositional environment (Djokic et al, 2017; Nijman et al, 1998; Van Kranendonk, 2006; Van Kranendonk et al, 2018; Van Kranendonk et al, 2008; Van Kranendonk & Pirajno, 2004; among others).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The texture and chemistry of this organic matter‐rich, texturally distinctive nano‐porous pyrite is consistent with an origin through sulfidization of biofilms as early as during stromatolite growth (c.f., Baumgartner, Van Kranendonk, et al, 2020; Baumgartner et al, 2019), as is supported by the presence of entombed, autochthonous organic matter strands and filaments that closely resemble variably degraded and remineralized EPS (compare the organic matter that is encrusted by barite micro‐spherulites in Figure 3f with organic matter strands in Baumgartner et al[2019, their Figure 4]). Hence, while all the physical and chemical factors that can control barite morphology are still not entirely understood (c.f., Widanagamage et al, 2018), our data suggest that intimately associated organics have been important factors for micro‐spherulite formation. These organics were likely derived from (decaying) ancient microbial mats that flourished in a hydrothermally influenced, low‐temperature, shallow water depositional environment (Djokic et al, 2017; Nijman et al, 1998; Van Kranendonk, 2006; Van Kranendonk et al, 2018; Van Kranendonk et al, 2008; Van Kranendonk & Pirajno, 2004; among others).…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, barite in the water column and within pelagic sediment typically occurs as rounded, elliptical, or platy tabular grains (e.g., Bertram & James, 1997; Dehairs, Stroobants, & Goeyens, 1991; Griffith & Paytan, 2012). Although the detailed factors in the development of a specific barite morphotype are not entirely understood, laboratory experiments show that variations can be controlled by physical factors such as saturation index, crystal growth rate, and temperature, as well as chemistry, especially the ratio of Ba 2+ /SO4 2− in solution, the presence/abundance of organic molecules, and the availability of ions that may substitute for Ba 2+ in the crystal lattice (Mg 2+ , Ca 2+ , and Sr 2+ ; e.g., Godinho & Stack, 2015; Jones et al, 2007; Judat & Kind, 2004; Kowacz, Putnis, & Putnis, 2007; Ruiz‐Agudo, Putnis, Ruiz‐Agudo, & Putnis, 2015; Smith et al, 2004; Widanagamage, Waldron, & Glamoclija, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…where a(Ba 2+ ) and a(SO 4 2− ) are the activities of Ba 2+ and SO 4 2− , respectively, K sp is the solubility product of barite. For barite, K sp is 9.82 × 10 −11 at 25 • C [8]. Previous work has demonstrated that at high reagent supersaturation ratios (the natural logarithm of supersaturation ratio, lnS = 16.97), a large number of very small spherical nanoparticles will be formed.…”
Section: Effect Of Supersaturation On the Morphology Of Baritementioning
confidence: 98%
“…Early Earth's marine environments were anoxic and sulfate deposits prevailed, resulting in barite as the dominant or the only sulfate mineral within bedded sulfate deposits older than 2.4 Ga [3][4][5][6][7]. Due to its high density and strong resistance to chemical weathering, barite is present throughout Earth's history and has the potential to preserve a record of conditions attending formation, which could be useful for interpretations of Earth's ancient rocks and paleoenvironments [8].…”
Section: Introductionmentioning
confidence: 99%